THE INFLUENCE OF ORGANIZATIONAL STRUCTURE ON M-COMMERCE PERFORMANCE IN KENYA'S COMMERCIAL BANKS - Muriu, Dr. Doreen (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of the study was to explore the influence of organizational structure on Mobile-Commerce (M-Commerce) performance in Kenya's commercial banks. Methodology: The study adopted a positivism research philosophy and descriptive research design. The technique used was stratified random sampling. A sample of 133 managers from a target population of 200 was picked. Structured questionnaires were used to collect the required data. For data collection procedure, the researcher recruited research assistants who dropped and picked the questionnaires from the banks. Findings The study findings indicated that, path coefficient value was 0.237, thus the relationship between organizational structure and m-commerce performance was positive and significant (t = 3.553, p =0.000). The study correlated organizational structure and m-commerce performance and found that organizational structure and m-commerce were positively and significantly related at the 0.01 level (2-tailed). Unique Contribution to theory, practice and policy: Organizational structure is very important in enabling improved performance of m-commerce The study recommends that banks modify their structures to support strategy implementation. This result showed that m-commerce performance or growth increased with a supportive structure.